Mold contamination in a controlled hospital environment: a 3-year surveillance in southern Italy - Caggiano, Giuseppina (BMC Infect Dis, 2014)
BACKGROUND: Environmental monitoring of airborne filamentous fungi is necessary to reduce fungal concentrations in operating theaters and in controlled environments, and to prevent infections. The present study reports results of a surveillance of filamentous fungi carried out on samples from air and surfaces in operating theaters and controlled environments in an Italian university hospital. METHODS: Sampling was performed between January 2010 and December 2012 in 32 operating theaters and five departments with high-risk patients. Indoor air specimens were sampled using a microbiological air sampler; Rodac contact plates were used for surface sampling. Fungal isolates were identified at the level of genera and species. RESULTS: Sixty-one samples (61/465; 13.1%) were positive for molds, with 18 from controlled environments (18/81; 22.2%) and 43 (43/384; 11.2%) from operating theaters. The highest air fungal load (AFL, colony-forming units per cubic meter [CFU/m(3)]) was recorded in the ophthalmology operating theater, while the pediatric onco-hematology ward had the highest AFL among the wards (47 CFU/m(3)). The most common fungi identified from culture of air specimens were Aspergillus spp. (91.8%), Penicillium spp., (6%) and Paecilomyces spp. (1.5%). During the study period, a statistically significant increase in CFU over time was recorded in air-controlled environments (p = 0.043), while the increase in AFL in operating theaters was not statistically significant (p = 0.145). Molds were found in 29.1% of samples obtained from surfaces. Aspergillus fumigatus was the most commonly isolated (68.5%). CONCLUSIONS: Our findings will form the basis for action aimed at improving the air and surface quality of these special wards. The lack of any genetic analysis prevented any correlation of fungal environmental contamination with onset of fungal infection, an analysis that will be undertaken in a prospective study in patients admitted to the same hospital. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12879-014-0595-z) contains supplementary material, which is available to authorized users.